2000
DOI: 10.1203/00006450-200002000-00011
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Maternal Smoking on Autonomic Nervous System in Healthy Infants

Abstract: To determine the influence of maternal smoking on autonomic nervous system in healthy infants, 36 infants were recorded polygraphically for one night. Their mothers were defined, according to their smoking frequency during pregnancy, as "nonsmokers" (no cigarettes smoked during pregnancy) or "smokers" (10 or more cigarettes per day). The infants had a median postnatal age of 10.5 wk (range 6 to 16 wk); 18 were born to nonsmokers, and 18 to smokers. During the whole night, spectral analyses of heart rate (HR) w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
53
1

Year Published

2001
2001
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 99 publications
(59 citation statements)
references
References 49 publications
5
53
1
Order By: Relevance
“…Still, the effects were dose-dependent and consistent across type of chemoreceptor stimulus and direction of ventilatory change during a 3-month age span. Our findings are in accordance with previous work indicating that cigarette smoke exposure may influence autonomic nervous function even in apparently healthy individuals, both before birth (39), in infants (40), and in adults (23)(24)(25)(26). In a situation with heavy exposure, individual high susceptibility, a vulnerable developmental period, or the presence of disease, it is possible that cigarette smoke exposure could affect infant HR control critically.…”
supporting
confidence: 82%
“…Still, the effects were dose-dependent and consistent across type of chemoreceptor stimulus and direction of ventilatory change during a 3-month age span. Our findings are in accordance with previous work indicating that cigarette smoke exposure may influence autonomic nervous function even in apparently healthy individuals, both before birth (39), in infants (40), and in adults (23)(24)(25)(26). In a situation with heavy exposure, individual high susceptibility, a vulnerable developmental period, or the presence of disease, it is possible that cigarette smoke exposure could affect infant HR control critically.…”
supporting
confidence: 82%
“…In addition, a growing body of research has documented an association between prenatal exposure to cigarettes and deficits in affective behaviors and regulation. Exposed infants have been found to show deficits in arousal and attention throughout the first year of life (Franco et al, 1999;Franco et al, 2000;Fried & Makin, 1987;Jacobson, Fein, Jacobson, Schwartz & Dowler, 1984;Picone, Allen, Olsen, & Ferris, 1982;Saxton, 1978;Schuetze & Eiden, 2006;Schuetze & Zeskind, 2001;Streissguth, Barr, & Martin, 1983). Studies have also found differences in affective behaviors among exposed infants as compared to nonexposed infants as early as the neonatal period and persisting into childhood.…”
mentioning
confidence: 99%
“…1 Because sympathetic overreactivity and autonomic dysfunction more generally are involved in the initiation and progression of disease, [2][3][4][5] we undertook a 1-year follow-up study to track the natural history and to assess the likely impact of the incipient hyperreactivity seen in a smoker's newborn infant.…”
mentioning
confidence: 99%